Ethical teaching to build a culture of peace - Auris Villegas, David (2021)
This essay reflects on teaching ethics as a social engineer and builder of a citizenry with a culture of peace in the context of globalization and dehumanization. This study aimed to provide specific guidelines and strategies to consolidate and strengthen the teacher as a social creator and peace builder. Through listening, dialogue, and resolution of those problems of their reality, such as corruption, citizen insecurity, and social irresponsibility, assigning to education the construction of those new ideas that will allow creating a different reality from freedom and peace. as an ethical and supportive domain. Methodologically, this research has been carried out under the qualitative, descriptive, analytical, explanatory, and comparative approach, resorting to world leaders in peace culture issues. It is concluded that a culture of peace and experiential commitment is possible in the field of education focused on the ethical teacher.